Factors influencing implementation and performance of Universal primary education programme - Mutabaruka, Fredrick; Tushabomwe Kazooba, Charles; Kemeza, Imelda (Researchjournali’s Journal of Management, 2018)
In this study, a critical analysis of Factors Influencing Universal Primary Education (UPE) Programme Implementation and Performance is addressed: the case of Uganda reflecting on the realisation of UPE programme in 1997. The central question of this paper is whether there are factor influencing the implementation and performance of the UPE programme in Uganda. A combination of research methods have been used for example the questionnaires and interviews. Findings reveal that funding of UPE programme is still very low yet it influences a lot on implementation and performance of the programme, pupil-teacher and pupil-classroom ratios still remain above the internationally recommended standards of 40:1 in all public schools, human resource to carry out UPE programme activities is not to the required standard, teachers are not well motivated and teaching is not effective. The portioning process of UPE capitation grant desires to be revised from unit cost per child to the needs of the school, factoring in the setting and backgrounds of the pupils, and sensitization of parents to supplement the financing of school activities by contributing some funds.
The case of Uganda
Keywords: Implementation; Performance; Realisation; Universal Primary Education